PREFACE / ПРЕДГОВОР (ETIMA, 2024)
The Faculty of Electrical Engineering at University Goce Delcev (UGD), has organized the Second International Conference Electrical Engineering, Informatics, Machinery and Automation -Technical Sciences applied in Economy, Education and Industry-ETIMA. ETIMA has a goal to gather the scientists, professors, experts, and professionals from the field of technical sciences in one place as a forum for exchanging the ideas, strengthening the multidisciplinary research and cooperation, and promoting the achievements of technology and its impact on every aspect of living. We hope that this conference will continue to be a venue for presenting the latest research results and developments on the field of technology. Conference ETIMA was held as online conference. More than sixty colleagues contributed to this event, from five different countries with more than thirty papers.We would like to express our gratitude to all the colleagues, who contributed to the success of ETIMA’23 by presenting the results of their current research and by launching the new ideas through many fruitful discussions. We invite you and your colleague to attend ETIMA Conference in the future as well. One should believe that next time we will have opportunity to meet each other and exchange ideas, scientific knowledge and useful information as well as to involve as much as possible the young researchers into this scientific event.